2022
DOI: 10.3389/fsufs.2022.868870
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Smart Agriculture and Trade-Offs With Biodiversity and Crop Yield

Abstract: Biophysical evaluations of climate-smart agriculture (CSA) often overlook the potential interactions with and implications for biodiversity and ecosystem services, which are important determinants of food system resilience and sustainability. Drawing on a case study in the East Usambara Mountains, Tanzania, we compare the impacts of CSA with other agricultural management practices on invertebrate pest and natural enemy diversity, and the associated effects on crop damage and crop yield. We found that the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The disease is mainly caused by the oomycete P. cinnamomi but other pathogens and global climate change also contribute to accelerate the damages provoked by the oomycete. Currently, the use of disease-tolerant plants is considered an efficient and cost-effective alternative for managing plant diseases ( Tripathi et al., 2022 ). In woody species, yet, long periods are necessary to apply for conventional breeding programs ( Corredoira et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is mainly caused by the oomycete P. cinnamomi but other pathogens and global climate change also contribute to accelerate the damages provoked by the oomycete. Currently, the use of disease-tolerant plants is considered an efficient and cost-effective alternative for managing plant diseases ( Tripathi et al., 2022 ). In woody species, yet, long periods are necessary to apply for conventional breeding programs ( Corredoira et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A key avenue for future research would involve large scale studies to identify clear patterns in the relationship between landscape complexity and natural enemy activity and the ecosystem service delivered to sub-Saharan agricultural systems. Furthermore, recent evidence from SSA showed that natural enemy diversity in crop fields is dependent on the land management of neighbouring fields (Tripathi et al 2022). This highlights the need for further multi-scale studies to identify potential variation in biocontrol effectiveness across different land management contexts.…”
Section: Landscape Composition and Biocontrolmentioning
confidence: 99%
“…Biocontrol techniques have been applied to numerous crops and targeted a wide variety of pests in the region, yet there is a lack of understanding of how the effectiveness of biocontrol varies across different crop types and pest taxa (Ratto et al2022). Recent research in Tanzania found greater natural enemy diversity in fields surrounded by intercropped fields, suggesting spatial flow of potential biocontrol services across landscapes (Tripathi et al 2022), but the established relationship between landscape composition, natural enemies and pest regulation is almost entirely based on studies carried out in the global north, and very seldom in sub-Saharan regions where farmers are most exposed to food insecurity caused by crop pests (Steward et al 2014). This represents a key knowledge gap; more clarity is needed about the environmental factors affecting biocontrol performance in sub-Saharan Africa to better assist in smallholder farmer decision making, and to determine the broader indirect impact of pest management options on biodiversity compared to synthetic pesticides, both on a farm and at a landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…A key avenue for future research would involve large scale studies to identify clear patterns in the relationship between landscape complexity and natural enemy activity and the ecosystem service delivered to sub-Saharan agricultural systems. Additionally, recent evidence from SSA showed that natural enemy diversity in crop fields is dependent on the land management of neighbouring fields [29]. This highlights the need for further multi-scale studies to identify potential variation in biocontrol effectiveness across different land management contexts.…”
Section: (D) Biocontrol Effectiveness Compared To Synthetic Pesticidesmentioning
confidence: 99%
“…Biocontrol techniques have been applied to numerous crops and targeted a wide variety of pests in the region, yet there is a lack of understanding of how the effectiveness of biocontrol varies across different crop types and pest taxa [28]. Recent research in Tanzania found greater natural enemy diversity in fields surrounded by intercropped fields, suggesting spatial flow of potential biocontrol services across landscapes [29]. However, the established relationship between landscape configuration, natural enemies and pest regulation is almost entirely based on studies carried out in the global north and some global south regions [30], but very seldom in sub-Saharan regions where farmers are most exposed to food insecurity caused by crop pests [31].…”
Section: Introductionmentioning
confidence: 99%